Immobilization of Penicillin-G Acylase from Bacillus thuringiensis BD1 for Enhanced Amoxicillin Production Using Na-Alginate Entrapment - Dewi, Rizky Aulia Prasasti; Widyasti, Erma Widyasti; Dianursanti, Dianursanti; Sriherwanto, Catur; Kusumaningrum, Susi; Rahayu, Maya D.; Putra, Noorendra L.; Hasanah, Nuur F.; Sativa, Rizka G.; Setyahadi, Siswa; Nandyawati, Dewi (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Efficient enzymatic production, particularly using Penicillin-G Acylase (PGA), is crucial for synthesizing amoxicillin, a penicillin-type antibiotic. This study optimized PGA immobilization from Bacillus thuringiensis BD1 using Na-alginate to enhance stability and cost-effectiveness. Various Na-alginate concentrations (1%, 1.25%, 1.5%) were tested, with stability assessments at pH 6-9 and temperatures of 30-60 °C, alongside reusability, morphology, and amoxicillin synthesis evaluations. Initial activity was 46.59 U/mg, with optimal immobilization at 1.5% Na-alginate achieving 41.01 U/mg. After four uses, immobilized PGA BD1 retained ±20% activity with optimal conditions at pH 7 and 40 °C. Enhanced amoxicillin synthesis compared to free enzymes highlights its industrial potential. This research demonstrates the feasibility of using immobilized PGA BD1 for scaling up amoxicillin production, offering significant economic and technological benefits.